Simulation of a mechanical prototype for the extraction of soil sampling using PETG and PLA material - Culqui, Marcelo (2023)
Corn production in Perú during the last five years has been reduced for various reasons and the inefficient application of technology, because the progress of technology has been decreasing the intervention of the human hand in the field. For example, the use of automated pivot irrigation systems has had a positive impact on the efficiency of irrigation administered to the plants; however, this system has resulted in the neglect of the plants in the first months, generating a final production lower than that estimated for each harvest season. In view of this, the use of Unmanned Aerial Units (UAV) is proposed in order to collect soil samples around the cultivated field to be delivered to the laboratory for analysis. This mechanism consists of an arm with two degrees of freedom including an extractor that presents an auger with a worm inside, in turn it will have a rotational movement through a reduction box, the design will be manufactured in PLA and PETG material to be implemented in the UAV and perform extractions of samples of sand and soil present in Olmos, Lambayeque, Peru. In addition, this model includes a storage tank for the samples obtained to be able to perform up to three samples at different points during a single flight. The expected result is to obtain up to three samples in a range of 250 grams per extraction point in one flight, so the sampling depth will be 16 cm and a diameter of 6 cm.